POLA PERUBAHAN INTERAKSI DALAM KELUARGA PADA MASYARAKAT AIR BATUMBUK JALUR PENDAKIAN GUNUNG TALANG - sawatul zamra; rusdinal rusdinal; firman firman (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2020)
This article will explain and describe the position of Changingpatterns of interaction in the family of Air Batumbuk Mountain Climbing Talang Path.The theory that helps analyze the findings in this study is the social change from Veblen and Ogburn as technocratic people in a Materialistic perspective. Veblen sees society largely determined by technology. It primarily focuses on the technological influence on human thought and behavior.. This research used qualitative approach with descriptive research type. The technique of selecting informants with purposive sampling. The total number of informants is 10 people. Data were collected by interview, observation and documentation method. Interviews conducted are in-depth interview techniques and observations made are non-participation observation techniques. Data were analyzed by Miles and Huberman interactive analysis technique (Interactive analysis model) that is data reduction, data model and conclusion. The results of this study revealed the influence of technology that resulted in a change in interaction patterns in the area of Air Batumbuk Mountain Climbing Talang Path that is from the interaction directly (face to face) to the interaction using gadgets. Direct interaction at the present moment is only found in the evening only at dinner or watching television alone. In addition, changes in the pattern of interaction also affects the increasingly diminished parental power, giving greater attention to the child and the growing family function